26 Echocardiography and CMR-derived cardiac power-to-mass in asymptomatic patients with moderate-to-severe asymptomatic aortic stenosis versus healthy controls. (28th January 2023) - Haris, M; Marsh, Anna-Marie; Sian, Manjit; Aslam, Saadia; Pallikadavath, Susil; McCann, Gerry P; Singh, Anvesha
Abstract : Introduction: Cardiac power-to-mass (CPM) describes the hydraulic work done by the heart to maintain pressure in the arterial vasculature. It has been shown to have prognostic value in cardiac disease. Materials and Methods: In this prospective observational study, 112 asymptomatic patients with moderate to severe aortic stenosis (AS) (age 66 ± 12 years and 77% male) and 22 age- and sex-matched healthy controls (HC) underwent cardiac magnetic resonance imaging (MRI) and rest and exercise trans-thoracic echocardiography (TTE). CPM was calculated ([0.222 x cardiac output (CO) x mean arterial pressure]/LV mass) at rest and peak exercise during an incremental symptom-limited exercise test on a semi-supine ergometer. Peak CPM-rest CPM gave CPM reserve (CPMR). TTE-derived CO (heart rate x stroke volume) was calculated at rest and peak exercise, and both TTE and MRI-derived LV-mass were used to calculate CPM. Results: MRI-derived values were higher than TTE-derived and showed moderate to good correlation (Pearson's correlation coefficient: 0.6, 0.7 and 0.9) but poor to moderate agreement (ICC: 0.3, 0.4 and 0.6) for resting, peak and reserve CPM respectively. There was no difference in resting CPM between AS and HC measured by TTE or MRI. However, both TTE and MRI-derived peak CPM and CPMR parameters were significantly lower in AS: peak CPM 1.98±1.05W/100g vs 2.65 ± 0.86W/100g (TTE) and 3.2 ± 1.03W/100g vs 4.2 ± 0.85W/100g (MRI); and CPMR 1.10 ± 0.68W/100g vs 1.67 ± 0.68W/100g (TTE) and 1.79 ± 0.88W/100g vs 2.61 ± 0.79W/100g (MRI) in AS and HC respectively. Discussion: TTE underestimates CPM parameters due to overestimation of LV mass compared to the gold standard MRI, leading to poor agreement. Despite this, they show similar trends when comparing AS with HC. CPM parameters may be an important marker of subclinical disease and a potential risk-stratification tool in asymptomatic AS. Conclusion: Asymptomatic patients with AS demonstrate significantly lower peak CPM and CPMR compared to HC, despite normal values at rest, reflecting a lower functional exercise reserve. Acknowledgements: We acknowledge all sites that recruited patients in this multi-centre study.